Antibody persistence and booster response in adolescents and young adults 4 and 7.5 years after immunization with 4CMenB vaccine. Issue 9 (21st February 2019) - Nolan, Terry; Santolaya, Maria Elena; de Looze, Ferdinandus; Marshall, Helen; Richmond, Peter; Henein, Sam; Rheault, Paul; Heaton, Ken; Perrett, Kirsten P.; Garfield, Hartley; Gupta, Anil; Ferguson, Murdo; et al.
Highlights: 4–7.5 years post-2-dose 4CMenB primary series, 9–84% of subjects had hSBA titers ≥4 for ≥1 vaccine antigen. Antibody levels were higher in primed versus vaccine-naïve individuals of similar age. Post-booster, 93–100% of primed subjects had hSBA titers ≥4 against all antigens. Kinetics showed an early robust immune response at 7 days post-booster/second dose. The study raised no new safety concerns and overall, the vaccine was well-tolerated. Abstract: Background: Data on duration of protection against invasive meningococcal disease post-vaccination with the recombinant, 4-component, meningococcal serogroup B vaccine (4CMenB) are limited. We evaluated bactericidal activity persistence in adolescents/young adults up to 7.5 years post-primary vaccination with 4CMenB, and response to a booster dose compared with vaccine-naïve controls. Methods: This open-label, multicenter study (NCT02446743) enrolled 15–24 year-old-previously vaccinated participants from Canada, Australia (group Primed_4y) 4 years post-priming with 4CMenB (2 doses; 0, 1-month schedule), and Chile (Primed_7.5y) 7.5 years after priming with 4CMenB (2 doses; 0, 1/0, 2/0, 6-month schedule) and vaccine-naïve participants of similar age (Naïve_4y and Naïve_7.5y groups). Primed participants received a booster dose; vaccine-naïve participants received 2 catch-up doses of 4CMenB, 1 month apart. We evaluated antibody persistence and immune responses using hSBA in terms of geometric mean titers and percentages of participants with hSBA titers ≥4, the kinetics of bactericidal activity post-booster (previously vaccinated) or post-2 doses (vaccine-naïve), and safety. Results: Antibody levels declined at 4 (Primed_4y) and 7.5 (Primed_7.5y) years post-primary vaccination, but remained higher than in vaccine-naïve participants at baseline (≤44% vs ≤ 13% [fHbp]; ≤84% vs ≤ 24% [NadA]; ≤29% vs ≤ 14% [PorA]) for all vaccine antigens except NHBA (≤81% vs ≤ 79%). One month post-booster and post-second dose, 93–100% of primed and 79–100% of vaccine-naïve participants had hSBA titers ≥4 for all antigens. Kinetics of the antibody response were similar across groups with an early robust response observed 7 days post-booster/second dose. No vaccine-related serious adverse event was reported. Conclusion: For all antigens except NHBA, a higher proportion of primed participants had hSBA titers ≥4, at 4 and 7.5 years post-vaccination, compared with vaccine-naïve participants. A more robust immune response after booster compared to a first dose in vaccine-naïve individuals, showed effective priming in an adolescent/young adult population. No safety or new reactogenicity issues were identified. An Audio Summary linked to this article that can be found on Figshare: https://figshare.com/articles/Antibody_persistence_and_booster_response_in_adolescents_and_young_adults_4_and_7_5_years_after_immunization_with_4CMenB_vaccine/9437276 ; https://doi.org/10.6084/m9.figshare.9437276.v1 .